Outcomes of cardiac resynchronisation therapy in patients with heart failure with atrial fibrillation: a systematic review and meta-analysis of observational studies - Usman Mustafa; Jessica Atkins; George Mina; Desiree Dawson; Catherine Vanchiere; Narendra Duddyala; Ryan Jones; Pratap Reddy; Paari Dominic (Open Heart)
Background Cardiac resynchronisation therapy (CRT) is beneficial in selected patients with heart failure (HF) in normal sinus rhythm (NSR). We sought to evaluate the impact of CRT with or without atrioventricular junction (AVJ) ablation in patients with HF with concomitant atrial fibrillation (AF)Methods and results Literature was searched (inception through 30 August 2017) for observational studies that reported outcomes in patients with HF with CRT and AF that reported all-cause and cardiovascular mortality. Thirty-one studies with 83, 571 patients were included. CRT did not decrease mortality compared with internal cardioverter defibrillator or medical therapy alone in patients with HF and AF with indications for CRT (OR: 0.851, 95% CI 0.616 to 1.176, p=0.328, I2=86.954). CRT-AF patients had significantly higher all-cause and cardiovascular mortality than CRT-NSR patients ([OR: 1.472, 95% CI 1.301 to 1.664, p=0.000] and [OR: 1.857, 95% CI 1.350 to 2.554, p=0.000] respectively). Change in left ventricular ejection fraction was not different between CRT patients with and without AF (p=0.705). AVJ ablation, however, improved all-cause mortality in CRT-AF patients when compared with CRT-AF patients without AVJ ablation (OR: 0.485, 95% CI 0.247 to 0.952, p=0.035). With AVJ ablation, there was no difference in all-cause mortality in CRT-AF patients compared with CRT-NSR patients (OR: 1.245, 95% CI 0.914 to 1.696, p=0.165).Conclusion The results of our meta-analysis suggest that AF was associated with decreased CRT benefits in patients with HF. CRT, however, benefits patients with AF with AVJ ablation.